A Study On Pm10 On Health Impact Of Air Polution In Engineering Campus, Universiti Sains Malaysia - Sansuddin, Nurulliyana (Universiti Sains Malaysia, 2005)
Air pollution is a phenomenon that occurs on the earth and it includes Malaysia. It has always been happening ago. Many researches have measured types of pollutant including their sources and how they are distributed in the atmosphere and also the ways to reduce the problems. Research about particulate matter that assembles in the air especially in buildings is a new scenario. The situation where the possibility of the particulate matter is present in the building at this campus is the main cause of this research. As known, high concentration of particles in the air can affect the human health. There are varieties of illnesses caused by particulate matter such as asthma, respiratory problems, Chronic Obstructive Pulmonary Disease (COPD) and cancer. So, this research emphasized on monitoring indoor air pollution at 5 monitoring locations around the Engineering Campus, Universiti Sains Malaysia. The results of the concentration level of PM10 which are taken from the equipment called Microdust pro have been analyzed and it concludes that the concentration level of PM10 is under the limit that is fixed by the authorities. The highest average of the concentration reading is 49.4µg/m3 where it recorded at Rumah Kesatuan and the lowest reading is 2.8µg/m3 at Jaya Cafeteria. All of the data are less than the limit of the particulate matter which is 150µg/m3 for average concentration in 24 hours. There are some of the solutions that proposed in this research to reduce the concentration level before it gets worse in the future. The techniques are suggested to avoid the effect of the particulate matter especially to the human health at this campus.